1810 Value of Portable Transthorac Ultrasound to Aid Endotracheal Placement in Extremely Low Birth Weight Infants In the Delivery Room. (October 2012) - Philip, RK; Kenny, B; Ismail, A; Quinn, C
Abstract : Background and Aims: Correct endotracheal tube (ETT) position for extremely low birth weight (ELBW) neonates during initial resuscitation is critical. We aimed to, 1. Assess the feasibility and diagnostic utility of portable transthoracic ultrasound (PTU) to assess symmetry of diaphragmatic movement as a measure of correct ETT, 2. Assess PTU as a recordable accurate tool to document ETT position prior to surfactant administration to improve the 'golden hour management'. Methods: Single centre prospective study involving ELBW neonates < 1000 gm requiring intubation post-delivery. Two recordings per infant were done - one in delivery room and second when the infant reaches NICU. Accuracy of PTU (Micromaxx®) was compared with clinical assessments, colorimetric CO2 detection and Chest X-ray ETT position. Single operator conduced examinations who was not part of the resuscitation team. Hospital Research and Ethics committee approval was obtained. Results: Seventeen ELBW infants had PTU in labour delivery room (n=17) yielding 34 recordings. For 5 out of 17 (29.4%) infants significant improvement of ETT position could be offered by the use of PTU which otherwise was not detected. It is feasible to measure and record diaphragmatic excursion bilaterally during the labour ward resuscitation environment. The diagnostic accuracy of PTU for correct ETT was greater than that by traditional clinical methods and colorimetric CO2 detection. Inter-operator consistency and value of hand-held device (VScan®) is being evaluated. Conclusion: PTU is a valuable adjunct tool to record symmetry of diaphragmatic movement as a measure of correct ETT placement in labour ward for ELBW infants.